2009
DOI: 10.1016/j.neuron.2008.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Can We Share a Pain We Never Felt? Neural Correlates of Empathy in Patients with Congenital Insensitivity to Pain

Abstract: Theories of empathy differ regarding the relative contributions of automatic resonance and perspective taking in understanding others' emotions. Patients with the rare syndrome of congenital insensitivity to pain cannot rely on "mirror matching" (i.e., resonance) mechanisms to understand the pain of others. Nevertheless, they showed normal fMRI responses to observed pain in anterior mid-cingulate cortex and anterior insula, two key regions of the so-called "shared circuits" for self and other pain. In these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(110 citation statements)
references
References 60 publications
6
101
0
3
Order By: Relevance
“…Taken together, these and the present findings suggest that the first-hand experience of emotions is crucial and possibly even necessary for an accurate representation of other people's emotions (but see also ref. 33). However, the notion of functional equivalence and shared representations should not mistakenly imply that empathic and first-hand pain experiences rely on fully shared neural processes and psychological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these and the present findings suggest that the first-hand experience of emotions is crucial and possibly even necessary for an accurate representation of other people's emotions (but see also ref. 33). However, the notion of functional equivalence and shared representations should not mistakenly imply that empathic and first-hand pain experiences rely on fully shared neural processes and psychological functions.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it appears that individuals high upon this trait are particularly well equipped to fully engage in therapeutic efforts, (Quilty et al, 2008) and in this sense, be a good responder to treatment, even if it is placebo (Mackenbach, 2005). Interestingly, research in the mechanisms of empathy in the context of pain have shown responses to observed pain in mid-ACC and anterior insula, two key regions of the so-called 'shared circuits' for pain in self and that observed in others (Danziger et al, 2009). Given the overlapping neurobiology of pain, reward and placebo analgesia circuitry (Leknes and Tracey, 2008), it would not be surprising that regions engaged in empathic responses to others would also be involved in placebo responses.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there was no difference between the two groups in inferring pain from facial expressions, suggesting that personal experience of pain is not necessarily required to perceive-and feel empathy for-pain in others [5]. Interestingly, a recent fMRI study, conducted by the same group and reported in the January 2009 issue of Neuron, demonstrated that patients with congenital insensitivity to pain showed normal fMRI responses to observed pain in the anterior midcingulate cortex and anterior insula-regions which are activated in normal subjects when they experience real pain, or when they observe pain being administered to others [4]. So, we do not need to have experienced physical pain to be able to empathise with others, but we do need to feel pain in order to ensure that our body looks after itself.…”
Section: Feel Your Painmentioning
confidence: 99%